Disease involvement in the central compartment in eosinophilic chronic rhinosinusitis. Issue 10 (17th April 2021) - Makary, Chadi A.; Falco, Jeffrey; Sussman, Sarah; Ryan, Lindsey; Reyes, Camilo; Ramadan, Hassan; Kountakis, Stilianos E.
Abstract: Objective: To evaluate disease presence in the central compartment (CC) in patients with eosinophilic chronic rhinosinusitis (CRS). Methods: Patients with eosinophilic CRS were divided into three endotypes: aspirin‐exacerbated respiratory disease (AERD), allergic fungal rhinosinusitis (AFRS), and eosinophilic CRS with nasal polyps (eCRSwNP). CT scans were reviewed for CC involvement, defined as the area between the superior nasal septum (SNS) and middle turbinate (MT). CC involvement was measured based on the degree of opacification (0: no opacification, 1: up to 50% opacification, and 2: >50% opacification), and distance from SNS to MT (mm). Patients who had lateralized MTs from prior surgery as the cause of CC widening were excluded. Patients who underwent orbital decompression were included as a control group. Results: Fifty patients in each group (AERD, AFRS, and eCRSwNP) and 50 control patients were included. Average number of surgeries was 2.5 in AERD ( p = 0.05), 2 in AFRS ( p = 0.4), and 1.7 in eCRSwNP. Preoperative CC distance was significantly higher in AERD versus control, AFRS, and eCRSwNP: 4.2 versus 2.8 mm ( p < 0.0001), 4.2 versus 1.9 mm ( p < 0.0001), and 4.2 versus 2.7 mm ( p < 0.0001), respectively. Postoperatively, CC distance and degree of opacification were significantly higher in AERD versus control, AFRS, and eCRSwNP. Within the AERD group, CC distance was significantly higher postoperatively than preoperatively (6.5 vs. 4.2 mm, p = 0.002). Conclusion: CC involvement is more significant in AERD patients and if present, rhinologists should be suspicious of the diagnosis. This area could represent a source of inflammatory load in patients with AERD.